2022
DOI: 10.3390/antiox11050810
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ Activation Mitigates 6-OHDA-Induced Neuronal Damage by Regulating Intracellular Iron Levels

Abstract: Intracellular iron accumulation in dopaminergic neurons contributes to neuronal cell death in progressive neurodegenerative disorders such as Parkinson’s disease. However, the mechanisms of iron homeostasis in this context remain incompletely understood. In the present study, we assessed the role of the nuclear receptor peroxisome proliferator-activated receptor δ (PPARδ) in cellular iron homeostasis. We identified that PPARδ inhibited 6-hydroxydopamine (6-OHDA)-triggered neurotoxicity in SH-SY5Y neuroblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The glucagon-like peptide-1 receptor agonist liraglutide attenuated accumulation of intracellular iron by decreasing TfR1 expression and increasing FPN1 expression in db/db mice (Song et al, 2022). The peroxisome proliferator-activated receptor delta agonist GW501516 suppressed 6-hydroxydopamine-induced iron accumulation by regulating expression of DMT1 protein in SH-SY5Y cells (Lee et al, 2022). Biochanin A was also shown to suppress intracellular iron levels by regulating the expression of TfR1 and FPN1 in iron overloaded mice (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…The glucagon-like peptide-1 receptor agonist liraglutide attenuated accumulation of intracellular iron by decreasing TfR1 expression and increasing FPN1 expression in db/db mice (Song et al, 2022). The peroxisome proliferator-activated receptor delta agonist GW501516 suppressed 6-hydroxydopamine-induced iron accumulation by regulating expression of DMT1 protein in SH-SY5Y cells (Lee et al, 2022). Biochanin A was also shown to suppress intracellular iron levels by regulating the expression of TfR1 and FPN1 in iron overloaded mice (Ma et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“… 27 , 28 6-OHDA can also cause iron release from cytosolic ferritin and increase intracellular free iron concentration. 29 Since iron is involved in PD progression due to its pro-oxidant nature, the interruption of iron homeostasis by 6-OHDA could cause neuronal damage, especially in the substantia nigra (SN). 30 , 31 Our previous study found that 6-OHDA regulated the expression of iron-related proteins, increased cellular iron uptake and retention in N27 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 107 ] The elevated 4‐HNE in the cerebrospinal fluid (CSF) of PD patients is positively correlated with an increase of iron in the SN. [ 107 , 108 ] Recent studies have demonstrated that LPO is increased in PD in vitro and in vivo models induced by rotenone, [ 109 ] 6‐OHDA, [ 110 , 111 , 112 , 113 ] MPP + , [ 114 ] and MPTP. [ 115 ] Another study showed a direct association between endogenous α ‐synuclein ( α ‐syn) levels and the sensitivity of dopaminergic neurons to lipid peroxidation and ferroptosis via modulation of plasma membrane ether‐linked phospholipids.…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
“…Quercetin, [ 350 ] Dl‐3‐n‐butylphthalide, [ 109 , 351 ] β ‐hydroxybutyric acid, [ 352 ] thonningianin A, [ 112 ] GW501516 (a specific PPAR δ agonist), [ 111 ] hinokitiol, [ 113 ] paeoniflorin, [ 125 ] α ‐Lipoicacid, [ 114 ] iron chelator deferoxamine (DFO), [ 353 ] SK4/DFO, [ 354 ] clioquinol, [ 115 ] apoferritin, [ 126 ] ferrostatin‐1, [ 110 , 355 ] SK4/DFO, [ 354 ] and idebenone [ 356 ] alleviate PD through inhibiting ferroptosis (Table 1 ).…”
Section: Pharmacological Inhibition Of Ferroptosis To Treat Nds and S...mentioning
confidence: 99%